Security of intelligent edge computing:a survey - Xingshuo AN; Guixing CAO; Li MIAO; Shubo REN; Fuhong LIN (Dianxin kexue)
With the rise of edge computing,more and more attentions have been paid to security issues of edge computing.The basic concepts,system architecture and the relationship between edge computing and other computing paradigms were introduced.Then the security threats to edge computing were analyzed,and the security technology of edge computing was discussed for these security threats.Finally,the technologies of intrusion detection,access control,defense strategy and key management in edge computing were summarized and the further research directions were pointed out.